Effect of Ultrasonication on the Properties of Goat Milk Yogurt: Study on Amplitude and Duration - Nisa, Fithri Choirun; Widodo, Archangela Zevanya Venenzia (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract—The gel strength of yogurt from goat milk is weak due to the low as1-casein proportion. According to some studies, treating cow milk via ultrasonication before fermentation produces yogurt that is stiffer than regular yogurt. This study aimed to investigate the influence of amplitude and duration of ultrasonication on the properties of goat milk yogurt (pH, total acid, viscosity and syneresis). Scanning electron microscopy (SEM) was used for additional investigation to evaluate the microstructure of the best-treated sonicated goat milk yogurt and compared to non-sonicated goat milk yogurt. The results demonstrated that these two factors interacted to affect viscosity and that the amplitude and duration of sonication had a significant effect on total acid and syneresis. These two factors, however, had no appreciable impact on the pH. At an amplitude of 80% and duration of 10 minutes, the best treatment was attained and the sample had the following properties: pH of 4.38, total acid of 1.00%, viscosity of 4929.67 cP, syneresis of 13.31%, and 2.36 x 107 CFU/ml for the lactic acid bacteria colonies. In comparison to non-sonicated goat milk yogurt, the sonicated yogurt's microstructure was denser and more complex, which may contribute to the increased gel firmness.